Covid-19 risk perception impacts on behavioural intention towards Malaysia’s domestic tourism during the pandemic - Li Jingyi; Fumitaka Furuoka; Beatrice Lim; Khairul Hanim Pazim (Universiti Malaysia Sabah, 2020)
This study aims to explain domestic tourism's behavioural intention affected by individuals' COVID-19 risk perception during COVID-19 in Malaysia. Based on the discussion and analysis of the relevant literature, this study proposed a conceptual model that incorporates the theory of planned behaviour with the TRIRISK model to understand the relationship of behavioural intention to Malaysia’s domestic tourism and risk perception of COVID-19. Firstly, this paper pointed out that behavioural intention has been impacted by the multidimensional risk perception, including deliberative, affective, and experiential risk perception. Secondly, it stated that attitude, subjective norms, and perceived control behaviour significantly affect behavioural intention during the COVID-19 pandemic. Lastly, this paper also suggested that attitude, subjective norms, and perceived control behaviour mediate the perception of risk and behavioural intention. The paper presented a critical discussion that behavioural intention has been affected by risk perception. The conceptual model will be tested the validation by presenting the empirical data in the future study. From understanding tourists' behaviour change regarding the risk perception in COVID-19, this paper provides a vital reference for the Malaysia’s tourism industry and market. Moreover, this study also helps tourism practitioners develop practical and efficient strategies to recovery consumers’ confidence in the domestic tourism market and meet their needs and expectations for tourism products and services. This paper employed the TPB by incorporating the TRIRISK model to propose a conceptual model for explaining the individuals' behaviours change towards Malaysian domestic tourism in the context of the COVID-19 pandemic.